Pediatric Ventriculoperitoneal Shunt: Outcome Analysis in a Tertiary Care Center in Nepal - Phuyal, Suman; Rajbhandari, Binod; Pradhanang, Amit B; Sedain, Gopal; Shilpakar, Sushil K; Sharma, Mohan R (Journal of Institute of Medicine Nepal, 2020)
Introduction Ventriculoperitoneal (VP) shunt is a commonly performed neurosurgical procedure in pediatric surgical practice. It results in a dramatic improvement in patient survival and neurological function but is associated with several complications requiring multiple shunt revisions throughout a patient’s lifetime. The main aim of the study was to evaluate the outcome especially complications of shunt surgery at our center. Methods A single-institutional, retrospective observational study was conducted in 60 operated cases of congenital hydrocephalus with a minimum follow-up for up to 6 months. Parameters for analysis included demographic data, etiology of hydrocephalus, surgery time, and type of complications. Results Out of 86 patients, 60 patients who fulfilled the inclusion criteria were enrolled in the study. The mean age of the patients at the time of VP shunt placement was 3 months, range from 8 days to 15 years with male preponderance. The majority of the patients belonged to the 0-1-year age group (76.8%). The commonest etiology of hydrocephalus was congenital aqueduct stenosis. Fifteen patients (25%) developed complications within six months follow-up period. Eight patients (13.3%) developed clinical shunt infection with four cases having culture positive. Four (6.67%) had mechanical complications in the form of shunt obstruction. Three patients had ascites, subdural collection, and shunt extrusion from the anus. The shunt related mortality was 1.67%. Conclusion The shunt infection and obstruction still remain the most important complications. Despite inherent problems, shunt surgery is the procedure of choice until a safer effective alternative is available.